Hajj crowd tracking system in a pervasive environment - Mantoro, Teddy; Ayu, Media Anugerah; Mahmud, Murni (IGI Global, 2012)
Hajj is a huge congregation of muslims from all over the world which happens annually in Makkah, Kingdom of Saudi Arabia (KSA). It is one of the pillars of Islam and every able Muslim must perform this act at least once in their lifetime. Many challenges are faced by the organizers as well by the pilgrims during this massive religious gathering. The cases of missing Hajj pilgrims are not uncommon and although several tracking and navigation devices have been introduced, there is still a need for a better solution in overcoming the issue. There are several factors that prevent a widespread use of the system, such as the operational costs, availability of the connections and the use in uncommon platform. This paper proposes a framework for tracking Hajj pilgrims in a crowded pervasive environment using a system called HajjLocator. A discussion on the prototype of HajjLocator, as a system to track and monitor pilgrims while performing Hajj and to save alive, SOS mechanism, is also presented in this paper.